Sound from Silence. Recent Discoveries in Ancient Near Eastern Music - Kilmer, Anne Draffkorn (1976)
A stereo record album with a 24-page illustrated booklet; Box 9068; $16 ($19 outside U.S.A.); RS 15.30 + 15.49 + 17.387 and other musicological texts.